BONE RECONSTRUCTION TECHNIQUES WITH AUTOGENOUS GRAFTS: INDICATIONS AND DONOR SITE SELECTION CRITERIA (International Seven Journal of Multidisciplinary, 2026)
The long-term viability of dental implants is intrinsically linked to the presence of robust bone support. In cases of tooth loss resulting in severe resorption, ridge reconstruction becomes an indispensable step, and autogenous grafting is widely recognized as the gold standard due to its biological triad: osteogenesis, osteoinduction, and osteoconduction. This narrative review examines contemporary bone reconstruction techniques and the criteria for donor site selection, based on evidence collected from the PubMed database over the past ten years. The data indicate that, in addition to traditional autologous bone, the use of processed dental tissues (such as dentin) has emerged as an alternative with high biocompatibility and low morbidity, delivering solid clinical outcomes. In the management of horizontal defects in esthetic areas, the combination of bone chips with cortical barriers has proven effective in minimizing postoperative discomfort without compromising volumetric gain. On the other hand, cases of greater structural complexity may still require harvesting from extraoral sites. In summary, the success of regeneration lies in the clinician’s ability to select the technique that best balances the patient’s volumetric demand with biological preservation, reaffirming the superiority of the individual’s own tissue in achieving high-quality and stable newly formed bone.